Die Entstehung des Alten Testaments - Dietrich, Walter; Mathys, Hans-Peter; Römer, Thomas; Smend, Rudolf (W. Kohlhammer GmbH, 2014)
This teaching and textbook describes the biblical writings, first by content and structure, and then follows their process of coming into being back to the respective reason for their origin. The framework for this is the canon of the Hebrew Bible, which is defined in the introductory section by the Greek and Christian Bible and the so-called Apocrypha. The four parts of the volume are introduced by overview chapters: the Pentateuch as a whole, the Deuteronomistic historical work, the phenomenon of prophecy and Hebrew poetry. The author also appropriately discusses the progress and current state of research. Comprehensive bibliographies characterise the entire work. Anyone wishing to intensively examine the Old Testament and its origins will obtain sound information here. Dieses Lehr- und Studienbuch beschreibt die biblischen Schriften zunächst nach Inhalt und Aufbau und verfolgt dann ihren Werdeprozess zurück bis zum jeweiligen Entstehungsgrund. Den Rahmen gibt der Kanon der hebräischen Bibel vor, der im Einleitungsteil von der griechischen bzw. christlichen Bibel und den sog. Apokryphen abgegrenzt wird. Die vier Kanonteile werden durch Überblickskapitel eröffnet: der Pentateuch als ganzer, das deuteronomistische Geschichtswerk, das Phänomen der Prophetie, die hebräische Poesie. Gang und Stand der Forschung kommen angemessen zur Geltung. Umfassende Bibliographien durchziehen das Werk. Wer sich intensiv mit dem Alten Testament und seiner Entstehung befassen will, erhält hier fundierte Information